Dissolution and passivation of iron in acetonitrile and acetonitrile±water mixtures - Li, F.B.; Bremner, D.H.; Burgess, A.E.
The dissolution and passivation of iron in neutral acetonitrile-water mixtures have been studied under potentiodynamic and potentiostatic conditions. In ``dry'' acetonitrile (water content <0.02
Keywords: DISSOLUTION AND PASSIVATION OF IRON; ACETONITRILE-WATER MIXTURES; CORROSION IN ORGANIC SOL-VENTS; EFECTS OF PASSIVATORS; TRANSPASSIVE DISSOLUTION THROUGH 2D NUCLEATION AND GROWTH OF AN OXIDE RLM